Examining the factors for girls dropout in Meatu district council, - Damas, Juma (Mzumbe University, 2024)
A dissertation submitted to the School of Public Administration and Management in fulfillment of the requirements for the degree of Master of Science in Human Resource Management (MSc. HRM) of Mzumbe University